Relevansi Pendidikan Akhlak dalam Surat Luqman (31) Ayat 12-19 dengan Pendidikan Anak Kontemporer - Mubarak, Agus (Dinamika Ilmu, 2014)
Al-Qur’an, as a guidance of life is not doubtful at all, truly able to give a right direction for all human problems in this world, including how to educate the children. One of the directions and guidances about how to educate the children given by Al-Qur’an is Surat Luqman (31) verse 12-19. Based on the findings of this study, the researcher concludes that the content of ahlaq education for children stated in Surat Luqman (31) verse 12-19 are: (1) thankful to Allah, to parents, and to be a strong moslem; (2) devoting to the parents; (3) ordering to do the right things and avoiding the bad things; (4) be patient; and (5) do not arrogant. Those ahlaq content are still relevant to this contemporary children education.